2018
DOI: 10.2307/j.ctvckq52c
|View full text |Cite
|
Sign up to set email alerts
|

Tongue Root Harmony and Vowel Contrast in Northeast Asian Languages

Abstract: Roughly speaking, the above ten languages can be divided into two groups: the socalled "Paleosiberian" and "Altaic" language groups. Ainuic, Amuric, Kamchukotic, Yeniseic, and Yukaghiric belong to the first group (Comrie, 1981;Vajda, 2009) and Japonic, Koreanic, Monglic, Tungusic, and Turkic belong to the second group. This thesis focuses on the second group, especially Koreanic, Mongolic, and Tungusic languages, which have (or once had) a vowel harmony based on tongue root contrast.Turkic languages, another m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 115 publications
0
8
0
Order By: Relevance
“…Typologically, Kaun connects cross-linguistic patterns of labial harmony with the phonetic properties of round vowels (cf. Cole & Trigo 1988, Nevins 2010, Ko 2012 for analyses without functional grounding).…”
Section: Labial Harmonymentioning
confidence: 99%
“…Typologically, Kaun connects cross-linguistic patterns of labial harmony with the phonetic properties of round vowels (cf. Cole & Trigo 1988, Nevins 2010, Ko 2012 for analyses without functional grounding).…”
Section: Labial Harmonymentioning
confidence: 99%
“…In addition, it has been shown that ATR increases the bandwidth of F1 (Hess 1992), essentially widening the spectral range of the formant to absorb f0. 13 Tungusic languages have been claimed to exhibit retracted tongue root (RTR) harmony (Ko 2012). From the point of view of MT, RTR might be encoded as a convergence between F1 (which is raised) and F2, or as phonetic prominence associated with higher spectral tilt.…”
Section: (12)mentioning
confidence: 99%
“… 22 It is not immediately apparent that we can derive the difference between Mongolic and Tungusic languages from their vowel inventories, since Khalkha Mongolian (Mongolic) and Classical Manchu (Tungusic) have virtually the same inventories (see also Ko 2012 on this point).…”
mentioning
confidence: 99%